Intercropping sorghum and rice - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1987)
Intercropping sorghum with rice on areas liable to flooding can provide a more reliable harvest, without involving farmers in much extra work. In the Jonglei Province of Southern Sudan, sorghum or maize crops are often partly or entirely lost when...